How can implementation intentions be used to modify gambling behavior? - St Quinton, Tom (Frontiers in Psychology, 2022)
Problem gambling can cause significant harm, yet rates of gambling continue to increase. Many individuals have the motivation to stop gambling but are unable to transfer these positive intentions into successful behavior change. Implementation intentions, which are goal-directed plans linking cues to behavioral responses, can help bridge the gap between intention and many health behaviors. However, despite the strategy demonstrating popularity in the field of health psychology, its use in the area of gambling research has been limited. This mini review illustrates how implementation intentions can be used to facilitate change in gambling behavior. Adopting the strategy could help reduce the number of people with gambling problems.